2012
DOI: 10.1039/c1cp22823d
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between anions and substituted molecular bowls

Abstract: Complexes formed by anions and substituted molecular bowls were studied by means of computational methods. The bowls consisted of corannulene molecules substituted with five or ten F, Cl, or CN groups, whereas Cl(-), Br(-) and BF(4)(-) were the anions considered. Substitution with F, Cl and CN hardly affects the geometry of the bowl, but produces an inversion of the molecular electrostatic potential of the bowls, which becomes positive over the two faces of the bowl, therefore interacting favorably with anions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 57 publications
6
36
0
Order By: Relevance
“…[2,3,11,12,14] Also, anionÁÁÁp interactions between an anion and an electron-deficient aromatic system have recently aroused interest. [20,25] It has also been shown that aromaticity can change on ion complexation by aromatic species. [20,21] However, it has been shown that in cationÁÁÁp systems, the role played by polarization can be important, especially in extended aromatic systems, [22][23][24] where it can be the main responsible of the stability of a cationÁÁÁp complex.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…[2,3,11,12,14] Also, anionÁÁÁp interactions between an anion and an electron-deficient aromatic system have recently aroused interest. [20,25] It has also been shown that aromaticity can change on ion complexation by aromatic species. [20,21] However, it has been shown that in cationÁÁÁp systems, the role played by polarization can be important, especially in extended aromatic systems, [22][23][24] where it can be the main responsible of the stability of a cationÁÁÁp complex.…”
Section: Introductionmentioning
confidence: 99%
“…[20,21] However, it has been shown that in cationÁÁÁp systems, the role played by polarization can be important, especially in extended aromatic systems, [22][23][24] where it can be the main responsible of the stability of a cationÁÁÁp complex. [18,20,24,25] Polycyclic aromatic hydrocarbons (PAHs) have attracted much interest related to possible application to materials science. [20,25] It has also been shown that aromaticity can change on ion complexation by aromatic species.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…All studied compounds were shown to interact favorably with the anions Cl ¹ , Br ¹ , and BF 4 ¹ via the conjugated system, preferentially on the concave side. 32 Complementarily, Josa et al studied dimers of corannulene bearing electron-withdrawing groups for fullerene recognition. 33 Dos Santos et al investigated 13 fluorinated corannulenes ( Figure 5) by density functional theory calculations.…”
Section: Computational Studies On Electrondeficient Buckybowlsmentioning
confidence: 99%